Handbook of emerging market multinational corporations - edited by Mehmet Demirbag (Cheltenham Edward Elgar, 2015)
The Handbook of Emerging Market Multinational Corporations focuses on why emerging market multinationals internationalize, how they do so and the advantages they explore and exploit as they internationalize. The Handbook highlights the requirement for new perspectives on theory and managerial practice to better comprehend this phenomenon.
Includes bibliographical references and index.
Keywords: International business enterprises